The Phospholipase A1 Activity of Glycerol Ester Hydrolase (Geh) Is Responsible for Extracellular 2-12(S)-Methyltetradecanoyl-Lysophosphatidylglycerol Production in Staphylococcus aureus - Chitra Subramanian; Matthew W. Frank; My-Kyung Yun; Charles O. Rock (mSphere, 2023)
ABSTRACT Phosphatidylglycerol (PG) is the major membrane phospholipid of Staphylococcus aureus and predominately consists of molecular species with ≥16-carbon acyl chains in the 1-position and anteiso 12(S)-methyltetradecaonate (a15) esterified at the 2-position. The analysis of the growth media for PG-derived products shows S. aureus releases essentially pure 2-12(S)-methyltetradecanoyl-sn-glycero-3-phospho-1′-sn-glycerol (a15:0-LPG) derived from the hydrolysis of the 1-position of PG into the environment. The cellular lysophosphatidylglycerol (LPG) pool is dominated by a15-LPG but also consists of ≥16-LPG species arising from the removal of the 2-position. Mass tracing experiments confirmed a15-LPG was derived from isoleucine metabolism. A screen of candidate secreted lipase knockout strains pinpointed glycerol ester hydrolase (geh) as the gene required for generating extracellular a15-LPG, and complementation of a Δgeh strain with a Geh expression plasmid restored extracellular a15-LPG formation. Orlistat, a covalent inhibitor of Geh, also attenuated extracellular a15-LPG accumulation. Purified Geh hydrolyzed the 1-position acyl chain of PG and generated only a15-LPG from a S. aureus lipid mixture. The Geh product was 2-a15-LPG, which spontaneously isomerizes with time to a mixture of 1- and 2-a15-LPG. Docking PG in the Geh active site provides a structural rationale for the positional specificity of Geh. These data demonstrate a physiological role for Geh phospholipase A1 activity in S. aureus membrane phospholipid turnover. IMPORTANCE Glycerol ester hydrolase, Geh, is an abundant secreted lipase whose expression is controlled by the accessory gene regulator (Agr) quorum-sensing signal transduction pathway. Geh is thought to have a role in virulence based on its ability to hydrolyze host lipids at the infection site to provide fatty acids for membrane biogenesis and substrates for oleate hydratase, and Geh inhibits immune cell activation by hydrolyzing lipoprotein glycerol esters. The discovery that Geh is the major contributor to the formation and release of a15-LPG reveals an unappreciated physiological role for Geh acting as a phospholipase A1 in the degradation of S. aureus membrane phosphatidylglycerol. The role(s) for extracellular a15-LPG in S. aureus biology remain to be elucidated.